Harmonizacja i standaryzacja zasad rachunkowości w Unii Europejskiej a polskie prawo bilansowe - Bąk, Melania (Harmonization and standardization of accountancy standards in the European Union vs. Polish balance law, 2007)
Owing to harmonization and standardization of accountancy standards it is possible to take an international approach to accountancy. One of the main objectives of these processes is to present compatible financial statements, which exist and function in different conditions of balance law. European Union presents significant accomplishments in the stimulating the harmonization process of accountancy standards by issuing directives as the main instrument in this process. However, working out uniform standards has become feasible owing to International Accountancy Standards (IAS). Therefore EU commenced and continues the process of adjusting EU legislation to IAS. Polish balance law, in the period of 1994-2004, underwent great transformations. The first Polish Accountancy Act is, most of all, adjusted to EU directives while the newer, amended version adjusts Polish solutions, in the domain of accountancy, to IAS. Polish accession to EU standards (EU changed position) with reference to IAS application, as well as the changes in directives themselves resulted in further changes in balance law in relation to IAS. Having adjusted Polish legal regulations to EU solutions, the consolidated financial statements of public companies, starting from 2005, will be prepared according to IAS. The process of standardization and harmonization keeps going on and as a result one should expect further changes in balance law.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1186, s. 171-188